Comparison between the Clinical Pulmonary Infection Score and Modified Centre for Disease Control Criteria for Diagnosis of Ventilator-associated Pneumonia: A Cross-sectional Study - Aniket Debnath; Saikat Batabyal; Sumit Roy Tapadar; Arunabha Datta Chaudhuri (Journal of Clinical and Diagnostic Research)
Introduction: Ventilator-Associated Pneumonia (VAP) is a frequent complication of Mechanical Ventilation (MV). The incidence of VAP is not precisely known and ranges from 13 to 51 per 1,000 ventilator days. A uniform surveillance definition for VAP is not available. The Centre for Disease Control (CDC)/National Healthcare Safety Network (NHSN) and the Clinical Pulmonary Infection Score (CPIS) algorithms are widely used. Aim: To compare the modified CDC criteria and the CPIS algorithm for VAP. Materials and Methods: A cross-sectional study was conducted at the respiratory care unit of the Department of Respiratory Medicine at RG Kar Medical College and Hospital in Kolkata, West Bengal, India, over a period of 18 months, from January 2021 to June 2022. A total of 60 adult patients on MV for more than 48 hours, with a high index of suspicion for VAP, clinically and radiologically, were included in this study. The microbiological (bacteriological quantitative culture) and radiological profiles {CXR parenchymal opacities, Ultrasonography (USG) and Contrast-Enhanced Computed Tomography (CECT) thorax} of VAP infections were assessed and compared. Statistical analysis was conducted after entering the data into a Microsoft Excel spreadsheet. Results: Among the 60 patients, most were male (76.67%) and aged between 51 and 60 years (40%). A total of 48 (80%) patients had a positive CPIS score, while 42 (70%) had positive modified CDC criteria. A fair degree of concordance was found between the two algorithms. Pseudomonas was the most common organism identified in both early and late-onset VAP. Among all antibiotics, Polymyxin B was found to be sensitive to all the organisms. Conclusion: The VAP is the most frequent infection associated with Intensive Care Unit (ICU) admissions. Polymicrobial aetiology and MDR strains were found in a significant number of cases. In the present study, the CPIS criteria demonstrated a fair concordance with the modified CDC criteria and slightly better sensitivity than the modified CDC criteria in diagnosing VAP.